Investigating employee polychronicity, perceived leadership 4.0, and organizational support as predictors of organizational performance in the Fourth Industrial Revolution (4IR) Era - Adekanmbi, Foluso; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2023)
This paper examines the present 4IR’s predictive elements for sustaining organizational performance (OP) in the Nigerian banks. Therefore, in light of the existing 4IR, this article suggests strategies for improving and sustaining OP in the Nigerian banks. The report promoted a quantitative research method based on a survey study design. The findings indicated that, within the Nigerian banks in the 4IR, employees' polychronicity (EP), Leadership 4.0 (L4.0), and perceived organizational support (POS) significantly and jointly predicted the sustainability of OP. Thus, it is recommended that human resource professionals, organizational managers, and the Nigerian banking industry promote strategies for enhancing and maintaining organizational performance. These strategies include encouraging employees to adopt a polychronic mindset, increasing Leadership 4.0, and offering regular organizational support. Thus, this paper has recognized organizational support, Leadership 4.0, and employees’ polychronicity as significant influencers in predicting factors in sustaining organizational performance in the Nigerian banking business during the Fourth Industrial Revolution.